2022
DOI: 10.1186/s44201-022-00007-4
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing the emergency department’s role in oncologic care: a review of the literature on unplanned acute care

Abstract: Background The global prevalence of cancer is rapidly increasing and will increase the acute care needs of patients with cancer, including emergency department (ED) care. Patients with cancer present to the ED across the cancer care continuum from diagnosis through treatment, survivorship, and end-of-life. This article describes the characteristics and determinants of ED visits, as well as challenges in the effort to define preventable ED visits in this population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 73 publications
4
27
0
1
Order By: Relevance
“…Consistent with previous studies, we found that nationwide each year, 4.2% of all ED visits were made by patients with cancer. This rate was similar to the rate of ED visits reported for other conditions, such as congestive heart failure (4.0%), chronic kidney disease (3.5%), and cerebrovascular disease (3.7%) . We also found that between 2012 and 2019, the number of cancer-related ED visits increased by 67.1% compared with cancer incidence, which only increased by 7.5% .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with previous studies, we found that nationwide each year, 4.2% of all ED visits were made by patients with cancer. This rate was similar to the rate of ED visits reported for other conditions, such as congestive heart failure (4.0%), chronic kidney disease (3.5%), and cerebrovascular disease (3.7%) . We also found that between 2012 and 2019, the number of cancer-related ED visits increased by 67.1% compared with cancer incidence, which only increased by 7.5% .…”
Section: Discussionsupporting
confidence: 85%
“…This rate was similar to the rate of ED visits reported for other conditions, such as congestive heart failure (4.0%), chronic kidney disease (3.5%), and cerebrovascular disease (3.7%). 45 We also found that between 2012 and 2019, the number of cancer-related ED visits increased by 67.1% compared with cancer incidence, which only increased by 7.5%. 46,47 The disproportionate increase in the number of ED visits by patients with cancer has put a substantial burden on EDs that are already operating at peak capacity.…”
Section: Discussionsupporting
confidence: 57%
“…Describing post‐cancer diagnosis ED utilization has been studied, and anywhere from 2% to 4% of all ED visits are attributable toward persons with a diagnosis of cancer 20 . As cancer survival rates increase, the number of cancer‐related ED visits also increases, and future work is needed to improve cancer management in the ED and potentially reduce unnecessary ED visits 20,21 . Prior ED use among patients with cancer is the strongest independent predictor for future ED use after a new diagnosis 22 .…”
Section: Discussionmentioning
confidence: 99%
“… 20 As cancer survival rates increase, the number of cancer‐related ED visits also increases, and future work is needed to improve cancer management in the ED and potentially reduce unnecessary ED visits. 20 , 21 Prior ED use among patients with cancer is the strongest independent predictor for future ED use after a new diagnosis. 22 Since ICD‐coded cancer diagnoses require tissue sample and biopsy, little to no confirmed cancer diagnoses originate from an ED visit.…”
Section: Discussionmentioning
confidence: 99%
“…Projections estimate that the number of new cases in both sexes between 65 and 85 years old will raise from 9.95 million in 2020 to 17.7 million in 2040 8 . Approximately 4% of all adult ED visits in the US are for cancer-related complaints 9 .…”
Section: Epidemiology and Characterization Of Older Adults With Cance...mentioning
confidence: 99%